Epidemiological and clinical analysis, and outcomes of tuberculosis co-infection among people living with HIV in Türkiye (2014–2024) ClinSurv HIV cohort: A large case series - Ali Mert; Okan Derin; Esra Zerdali; Abdurrahman Kaya; Özlem Gül; Deniz Borcak; Ahmet Furkan Kurt; Meliha Meriç Koç; Bircan Kayaaslan; Ayşe Batırel; Alper Gündüz; İnci Yılmaz Nakir; et al. (PLoS ONE, 2025)
Background Tuberculosis (TB) is one of the most common opportunistic infections in people living with HIV (PLHIV). Mycobacterium tuberculosis may cause more TB in all stages of HIV infection than in the general population, with the incidence of TB and the spread of pulmonary TB to other organs increasing as the CD4 count decreases. Objective In this HIV cohort study, we aimed to evaluate the clinical features, diagnosis, and prognosis of TB among PLHIV in Türkiye. Materials and methods We conducted a retrospective cohort study to analyze clinical outcomes and identify determinants of mortality among people living with HIV (PLHIV) co-infected with tuberculosis. We included 264 patients diagnosed and treated for TB across six centers in Türkiye. We extracted clinical, demographic, laboratory, microbiological, and radiological data from patient medical records. To identify independent predictors of mortality, we performed multivariable logistic regression and reported the results as odds ratios (ORs) with 95% confidence intervals (CIs). Results Of the 9,687 PLHIV who were followed for 10 years, 2.7% (264 individuals) developed TB. The median age of these individuals was 40 years, and 89% were male. The prevalence of pulmonary TB only, extrapulmonary TB only, and the coexistence of pulmonary and extrapulmonary TB were 42.4%, 48.8%, and 8.7%, respectively. Opportunistic infections and cancers were found in 23% (62 out of 264) of patients with HIV/TB co-infection. Among patients with HIV/TB co-infection, 42% showed lymphadenopathy, with 70% of these cases being generalized. In patients who underwent chest CT scans (n=200), radiological patterns revealed post primary TB in 46%, primary TB in 36%, and miliary TB in 18%. The positivity rates of Ehrlich-Ziehl-Neelsen staining (EZN), polymerase chain reaction (PCR), and TB cultures in clinical samples were found to be 47.5%, 72.5%, and 53%, respectively. Most of our patients (95%) were given the standard TB treatment regimen (HRZE), with a paradoxical reaction observed in 11.6% of cases and hepatotoxicity occurring in 18% of cases. Age, CD4 count (<200 cells/mm3-late presenters), and thrombocytopenia were identified as independent risk factors for mortality in the 58 patients (22%) who died after diagnosis. Conclusion Even today, more than one fifth of patients with HIV–TB co-infection in our cohort died. Mortality was higher among individuals who presented late with tuberculosis disease, especially those with advanced immunosuppression (CD4 <200 cells/μL). These findings underscore the urgent need for early HIV diagnosis and systematic TB screening to reduce co-infection–related mortality and improve clinical outcomes.